Experimental and numerical study of hydrodynamic responses of a new combined monopile wind turbine and a heave-type wave energy converter under typical operational conditions. (1st July 2018) - Ren, Nianxin; Ma, Zhe; Fan, Tianhui; Zhai, Gangjun; Ou, Jinping
Abstract: This paper deals with a new concept by combining a monopile type wind turbine and a heave-type wave energy converter, that is referred as the 'MWWC' (Monopile-WT-WEC- Combination) system herein. Hydrodynamic responses of the MWWC system under typical operational seas cases have been investigated by using both time-domain numerical simulations and scale model tests (1:50). For the numerical model, hydrodynamic loads of the monopile and the WEC are calculated by the AQWA code, which is available for modeling multi-body systems including both mechanical and hydrodynamic couplings between the TLP and the WEC. The scale model tests have been done in State Key Laboratory of Costal and Offshore Engineering (SLCOE). The power-take-off (PTO) system of the WEC device is simulated by two nonlinear air-dampers. Main hydrodynamic characteristics of the MWWC system under typical operational sea cases have been clarified. The obtained wave power characteristic and maximum PTO damping force of the WEC are very helpful for the optimal design of the operational performance of the PTO system. Numerical and experimental results are presented and compared, and good agreements are achieved. Highlights: For the scale test model of the MWWC system, the WEC's PTO damping effect has been effectively simulated by two air-damper devices. The numerical model can effectively predict main hydrodynamic responses of the MWWC system, although the numerical model tends to slightly overestimate the responses of the MWWC system without well accounting for the viscous damping effect in the scale test model. The preliminary optimal PTO damping stiffness of the WEC device for the MWWC system has been proposed. The wind power production (from NREL 5 MW WT) makes main contributions to the total power production of the MWWC system, comparing with corresponding WEC wave power production. The threshold of WEC take-off Hs for the MWWC system is suggested to be 6 m without huge bottom slamming loads caused by the potential water exit and entry effect.